Yushania rubrovaginata (Poaceae, Bambusoideae), a new combination for Sasa rubrovaginata - Xing Li; Jing-Bo Ni; Mian Liang; Yi-Hua Tong; Nian-He Xia (PhytoKeys)
Sasa rubrovaginata is transferred to Yushania based on morphological and molecular evidence. The lectotype for S. rubrovaginata is designated. Besides, a revised description of this species and a key to the four Yushania species distributed in Cenwanlaoshan Mountain are also provided.